Western Stemmed Tradition Settlement–Subsistence and Lithic Technological Organization in the Catnip Creek Delta, Guano Valley, Oregon, USA. (2nd October 2021) - Reaux, Derek J.
ABSTRACT : Cave and rockshelter sites have long been the cornerstone of Western Stemmed Tradition (WST) research in the northwestern Great Basin; however, these sites likely offer a narrow view of Terminal Pleistocene and Early Holocene lifeways. Open-air sites dominate the WST record and are critical to our understanding of WST settlement–subsistence practices and technological organization. I present the results of a lithic technological, source provenance, and spatial analysis of the Catnip Creek Delta (CCD) Locality, Guano Valley, OR. The CCD Locality contains one of the densest concentrations of Paleoindian artifacts in the region. My results indicate that the CCD Locality WST assemblage is likely a product of numerous short-term occupations by residentially mobile groups who primarily used the location to replenish their lithic toolkit and as a hunting location.